Anxiety and fear of COVID-19 in the UK general population: A cross-sectional study. Issue 10 (10th March 2023) - Morgado-Toscano, Cristina; Gómez-Salgado, Juan; Fagundo-Rivera, Javier; Navarro-Abal, Yolanda; Rodríguez-Jiménez, Lucas; Climent-Rodríguez, José Antonio; Allande-Cussó, Regina
Abstract : There is still a generalized feeling of uncertainty in the population due to the coronavirus disease 2019 (COVID-19) pandemic, as restrictions on daily routines and social contact, accompanied by a large number of infections, negatively affect different areas of people's lives and, therefore, their mental health. The aim of the present study was to assess the presence of anxiety and fear of COVID-19 in the general UK population, using the Anxiety and Fear to COVID-19 Assessment Scale (Ansiedad y Miedo al COVID-19) (AMICO) scale. A descriptive, cross-sectional study based on a questionnaire was conducted in a sample of the UK general population in 2021. Socio-demographic and employment variables were included. The AMICO scale was included to measure fear and anxiety about COVID-19. The relationship between variables was studied with a categorical regression analysis. In general, participants regarded themselves as well-informed about the pandemic, although 62.6% had only received 1 dose of the vaccine. Regarding the AMICO scale the total score was 4.85 (out of 10; standard deviation 2.398). Women showed higher scores for the AMICO than men. The bivariate analysis revealed statistically significant differences in relation to self-confidence, amount of information received, and vaccination variables as related to the mean AMICO scores. An average level of anxiety and fear of COVID-19 is shown in the general UK population, which is lower than most of the studies that assessed the impact of the pandemic on the general population.